Multi-area economic dispatch by using differential evolution immunized ant colony optimization (DEIANT) - Marzuki N.H.; Rahmat N.A.; Mat Salleh J.; Otoh O.F. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Economic dispatch is an important issue within the electrical system in meeting the lowest cost of the system and is subject to transmission and operating constraints.The power system operation and planning economic dispatch required a reliable technique to achieve minimal cost in economic dispatch otherwise the objective to minimize the generation cost fail. The electrical transmission network does not make complete electricity generation in Single-area economic dispatch. Thus, to complete the economic dispatch for the power transmission system, the multi-area network is proposed. The Multi-Area Economic Dispatch(MAED) connects two or more areas through a tie-line. Each region has a specific cost and load pattern. Tie-lines are used as connectors to enable power switching between regions. 31-Bus test system tested using an algorithm known as Differential Evolution Immunized Ant Colony Optimization (DEIANT) with different case studies with several trials taken to assess the consistency of results. Comparative studies with Pre-Optimization and Newton Rap son revealed that DEIANT technique is more reliable for multi-area power system network. BEIESP.